Long non-coding RNA GAS5 in human cancer - Yang, Xiaoyan; Xie, Zhizhong; Lei, Xiaoyong; Gan, Runliang (Oncology letters, 2020)
Long non-coding RNAs (lncRNAs) constitute a group of >200-nucleotide ncRNA molecules. lncRNAs regulate several cell functions, such as proliferation, apoptosis, invasion and metastasis. Meanwhile, lncRNAs are abnormally expressed in human malignancies, where they suppress or promote tumor growth. The present study focused on growth arrest-specific transcript 5 (GAS5), a well-known lncRNA that acts as a tumor suppressor but is suppressed in multiple types of cancer, including mammary carcinoma, prostate cancer, colorectal cancer, gastric cancer, melanoma, esophageal squamous cell carcinoma, lung cancer, ovarian cancer, cervical cancer, gliomas, osteosarcoma, pancreatic cancer, bladder cancer, kidney cancer, papillary thyroid carcinoma, neuroblastoma, endometrial cancer and liver cancer. Notably, GAS5 is overexpressed in liver cancer, potentially functioning as an oncogene. In the present study, the diagnostic and therapeutic roles of GAS5 in different tumors were reviewed, with a summary of the potential clinical application of the lncRNA, which may help identify novel study directions for GAS5.